Heat production and volatile biosynthesis are linked via alternative respiration in Magnolia denudata during floral thermogenesis - Wang, Ruohan; Chen, Ling; Jia, Yaping; Liu, Liya; Sun, Liwei; Liu, Yujun; Li, Yun (Frontiers in Plant Science, 2022)
Floral thermogenesis is coupled with odor emission in known thermogenic plants. It is widely accepted that elevation in floral temperature can help release of volatile organic compounds (VOCs). However, no information is available about whether floral thermogenesis is associated with VOC biosynthesis. Here, we used RNA-Sequencing (RNA-Seq) to draw a gene expression atlas of floral thermogenesis in Magnolia denudata and captured an upregulation of Alternative Oxidase (AOX) during floral thermogenesis. Western blot analyses also suggested upregulation of AOX during floral thermogenesis. Moreover, oxygen consumption analyses revealed increased activity of the AOX respiration pathway during floral thermogenesis. Using HPLC analyses, we further found that increased AOX respiration substantially promoted production of citric acid by 1.35 folds, which provided fundamental metabolite skeletons for biosynthesis of VOCs. RNA-Seq also showed upregulation of genes regulating lignin catabolism, which was in agreement with in situ Raman chemical imaging of lignin. Taken together, our results suggest the central role of AOX by coupling heat production and VOC biosynthesis in floral thermogenesis of M. denudata.